Leaders, Factions and Electoral Success - Benoit S Y Crutzen; Sabine Flamand (Tinbergen Institute, 2021)
We develop a formal model of the internal game between the leader and the factions of a party, to study the effect of party leadership on electoral success. Factions are of interest or of principle. The probability of winning an election is increasing in the leader's charisma, but also in party unity and coherence and in the factions' total contributions to party work and electoral efforts. To push factions to contribute, the leader offers both types of factions their favorite rewards in exchange for their contributions. We show that party unity and factions' total contributions are not necessarily increasing in the leader's charisma and ideological proximity to factions. Further, we show that factions of interest constraint the party's electoral strategy less than factions of principle. In particular, factions of interest always contribute more than factions of principle, are less of an obstacle towards achieving party unity, and offer the party more freedom in its choice of the ideological location and charisma of the party leader.
Keywords: D72; C72; 330